Protection of Medical Personnel and Health Facilities in Palestinian-Israeli Armed Conflict in International Humanitarian Law and Conflict Theory Perspective - Maulida, Yumna Nur; Dar Nasser, Montaser Faris; Mujib, M. Misbahul (UIN Sunan Kalijaga Yogyakarta, 2024)
The purpose of this study is to analyze both the protection of health facilities and the rights of medical personnel during the 2023 conflict between Palestine and Israel, as well as to investigate the causes of violations against these protections and rights. Protecting health facilities and medical personnel in the war between Palestine and Israel is a daunting task with all the consequences and death threats that can occur. In 2023 there have been several cases of attacks on hospitals and doctors being shot dead in Gaza City. This study employed doctrinal and hermeneutic methods with the theory of international humanitarian law and human rights theory, as well as conflict theory, to explain the causes of human rights violations despite the existence of international humanitarian law. The results of this study prove that there are still many violations of international humanitarian law, especially the 1949 Geneva Convention regarding legal protection for health facilities and medical personnel on the battlefield. This is due to the conflict of interest between countries or ethnicities, where both the state and ethnic Israelis and Palestinians feel threatened by each other's existence. Capitalist orientation also exacerbates ethnic class differences and creates power imbalances. Economic motives to compete for territory, natural resources, and power can easily lead to violations of non-combatant rights, including those of health facilities and medical personnel.